A study of prevalence and associated risk factors of hypertension in urban health training center: a cross-sectional study - Patil, Santosh D.; Ganganahalli, Praveen; Yenkanchi, Sandeep (International Journal Of Community Medicine And Public Health, 2024)
Background: WHO estimates that, 57 million disabilities adjusted lifetimes are attributed to hypertension. The global health overlook data reported that the age standardized frequency of hypertension is 24.1% and 20.1% for males and females respectively. Objectives were to find out the prevalence of hypertension in the urban field practice area and to study the risk factors associated with hypertension. Methods: A community based cross-sectional study was carried out in urban field practice area of medical college. Sample size of 350 participants of age more than 19 years residing in study area. Data collected by using simple random sampling by house-to-house visit. A pre-structured and pretested questionnaire used to interview the patients after obtaining their consent. The data was analyzed using SPSS. Results: 51.9% were having normal BP, 18.5% were having prehypertension, 19.7% were having stage-I HTN and 9.9% of the subjects were having stage-II HTN. Overall prevalence of hypertension in the study population was 29.6%. The prevalence of HTN was 32.42% in subjects who had family history of hypertension when compared to 33% in subjects who do not have a positive family history. In the present study, prevalence of HTN was 62% in past smokers compared to 33% in current smokers and 10% in nonsmokers. Conclusions: There is a significant burden of hypertension in urban areas. Age, education, and overcrowding were independent risk factors of hypertension in the present study. This study projects the need of an early detection of hypertension at the community level, which can be achieved by repeated periodic screening of the individuals.